Aerobic threshold and racing-skiers (young men) cardiac system potentialities determination and estimation on the basis of step-increasing bicycle ergometer load use - Petrov R. E.; Mutaeva I. S.; Ionov A. A. (The Russian Journal of Physical Education and Sport, 2018)
At the present stage of development skiing went through many qualitative changes, concerning the speed of distance overcoming and the technique of skiing. Equipment development and more qualitative skiing tracks helped racing skiers increase the effectiveness of performances. In this connection the demands concerning athletes` functional side of readiness also increased. The article is about methodological aspects of the correspondence determination ways and estimation between potential working capacity of cardiac system and maximum oxygen consumption and racing skiers` qualification level. Materials. The research was held on the base stage of sports training preparatory period among male teen-agers racing skiers. The test on "eBike" bicycle ergometer (Russia) was held. The initial load was 30 watt. The test was fulfilled in terms of step-increasing load, where the load was increasing 15 W more every minute. Research methods: scientific-methodical literature analysis, pedagogical observation, testing, estimation, mathematical research results handling. Results. Aerobic heart rate threshold and the power of maximum-aerobic capacities of legs muscles were determined, taking into account body weight. The estimation of relative potential heart working capacity was calculated and then created in W/kg in terms of heart rate 190 beats/min., taking into consideration maximum oxygen consumption (MOC) among racing skiers (young men).The estimation for relative power of maximum-aerobic capacities of legs muscles in W is created, taking into account body weight in case heart rate is 180 beats/min.. Conclusion. The test with step-increasing load helps to receive urgent information for aerobic threshold, potentiality of cardiac working capacity estimation, in case of increasing loads among racing skiers (young men). The results of the test prove that before the preparatory period all skiers are at a low level of functional and physical readiness. The estimation of heart relative potential working capacity is created in W/kg in terms of heart rate 190 beats/min., taking into account maximum oxygen consumption (MOC) for racing skiers (young men). Such kind of an approach helps to correct timely the volume and intensity of the training and competitive loads.